Pengaruh Pemberian Kompres Hangat terhadap Suhu Tubuh Pasca Imunisasi Pentabio di Wilayah Kerja Puskesmas Beruntung - Marsha Dwi Juliana; Hairiana Kusvitasari; Nita Hestiyana (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
DPT-HB-Hib immunization is part of the basic immunization program for infants aged 2–4 months and may cause post-immunization adverse events, particularly mild fever. Appropriate management of post-immunization fever is necessary to maintain infant comfort, including non-pharmacological approaches such as warm compresses. This study aimed to analyze the effect of warm compress application on changes in body temperature among infants after pentabio immunization in the working area of Beruntung Raya Community Health Center. This quantitative study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 10 infants aged 2–4 months selected using purposive sampling. Body temperature was measured before and after the warm compress intervention using a digital axillary thermometer and analyzed using a paired samples t-test with a significance level of 0.05. The results demonstrated a decrease in the mean body temperature of infants following the warm compress intervention, with statistical analysis indicating a significant difference between pre- and post-intervention body temperatures (p < 0.05). In conclusion, warm compress application has a significant effect on reducing body temperature in infants after pentabio immunization and may be considered an effective non-pharmacological intervention for managing mild post-immunization fever.